Reimbursed medication adherence enhancing interventions in 12 european countries: Current state of the art and future challenges - Kardas, Przemysław; Bago, Martina; Barnestein-Fonseca, Pilar; Garuolienė, Kristina; Granas, Anne Gerd; Gregório, João; Hadžiabdić, Maja Ortner; Kostalova, Barbora; Leiva-Fernández, Francisca; Lewek, Pawel; Mala-Ladova, Katerina; Schneider, Marie Paule; et al. (Frontiers in Pharmacology, 2022)
Background: Medication non-adherence jeopardises the effectiveness of chronic therapies and negatively affects financial sustainability of healthcare systems. Available medication adherence-enhancing interventions (MAEIs) are utilised infrequently, and even more rarely reimbursed. The aim of this paper was to review reimbursed MAEIs across selected European countries. Methods: Data on reimbursed MAEIs were collected from European countries at the ENABLE Cost Action expert meeting in September 2021. The identified MAEIs were analysed and clustered according to their characteristics, direct vs. indirect relation to adherence, and the targeted adherence phase. Results: Out of 12 contributing countries, 10 reported reimbursed MAEIs, 28 in total, of which 20 were identified as MAEIs targeting adherence directly. Reimbursed MAEIs were most often performed by either doctors (n = 6), nurses (n = 6), or pharmacists (n = 3). The most common type of MAEIs were education (n = 6), medication regimen management (n = 5), and adherence monitoring feedback (n = 4). Only 7 reimbursed MAEIs were technology-mediated, whereas 11 addressed two interlinked phases of medication adherence, i.e., implementation and persistence. Conclusions: Our review highlights the scarcity of reimbursed MAEIs across the selected European countries, and calls for their more frequent use and reimbursement.